Aktivitas Antioksidan Ekstrak Etanol Batang, Daun, dan Akar Kopasanda (Chromolaena odorata L.) dengan Metode FRAP (Ferric Reducing Antioxidant Power): Antioxidant Activity of Ethanol Extract of Stems, Leaves, and Roots of Kopasanda (Chromolaena odorata L.) with FRAP (Ferric Reducing Antioxidant Power) Method - Astuti Amin; Nur Khairi; Wahyu Hendrarti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Kopasanda (Chromolaena odorata L.) is a plant that contains flavonoid compounds that can act as antioxidants. This study aims to determine the antioxidant potential of the ethanol extract of the stems, leaves and roots of kopasanda by looking at the IC50 value. The stems, leaves and roots of Kopasanda were extracted by maceration using 70% ethanol as solvent. The results of the antioxidant activity test using the FRAP (Ferric Reducing Antioxidant Power) method showed very strong antioxidant activity with IC50 values ??of leaves 23.4 µg/ml, stems 37.556 g/ml and roots 36.860µg/ml with positive control of quarcetin, IC50 values ??were 2.724 g/ml . Based on these results, it can be said that the stems, leaves and roots have very strong antioxidant activity against the reduction of FRAP (Ferric Reducing Antioxidant Power).